Estimating glomerular filtration rate in African populations - Fabian, June (African Journal of Nephrology, 2023)
Without a strong bedrock of kidney research in African populations we are vulnerable to extrapolating research findings performed in non-African ancestry populations, mostly in high-income countries, with short- and long-term implications for individual and public health. This review tracks the evolution of kidney function testing, highlighting measured and estimated glomerular filtration rate (GFR) testing. While measured glomerular filtration rate (mGFR) is the most accurate method, there are potential sources of error for each reference compound and regional preferences and availability dictate choice. Establishing measured GFR testing as a research or clinical service is challenging and remains a barrier to mGFR testing availability in Africa. Estimated GFR is more practical but less accurate, and important for clinicians to understand the trade-offs, especially in an African context. Non-GFR determinants of serum creatinine lead to random error in measurement that is not a true reflection of kidney function: hereditable factors influence biomarker metabolism and excretion; biological variation results in intra-and inter-individual error; non-renal physiological factors include sex, age, environmental temperature (especially hot climes), ingestion of animal protein, levels of exercise, acute illness, chronic liver disease, enhanced gastrointestinal excretion with declining GFR, and concomitant medication that interferes with tubular handling of creatinine. There are likely to be additional factors (still unknown) in African populations; and analytic error that includes Jaffe vs enzymatic, use of standard reference materials and methods for calibration, and adherence to internal and external quality assurance programmes. Laboratories also require age and sex-based population-appropriate reference intervals for creatinine in children, adolescents, adults, and older adults which do not exist in many African countries. While the spotlight on racialised coefficients for eGFR has been largely confined to the USA, the impact of using GFR estimates that are US-based (and their racialised coefficients), throughout Africa remains overlooked. In Africa, recommended equations overestimate GFR, fewer individuals with CKD are diagnosed, and population prevalence is underestimated. Downstream, there are fewer opportunities to investigate causes or initiate treatment to prevent progression – much more relevant since the advent of sodium-glucose co-transporter 2 (SGLT-2) and glucagon-like peptide (GLP)-1 agonists for managing early CKD.